Anesthesia in PET/MRI. Challenges for the Anesthesiologist: A Narrative Review - Venkataramaiah, Sudhir; Venkatapura, Ramesh J.; Nagaraj, Chandana (Journal of Neuroanaesthesiology and Critical Care, 2024)
Positron emission tomography magnetic resonance imaging (PET/MRI) is an advanced imaging modality that combines metabolic information obtained from PET with anatomical and functional details obtained from MRI. This hybrid imaging technique offers superior spatial and temporal resolutions, making it invaluable in clinical and research settings. This review explores the considerations and strategies for administering anesthesia during PET/MRI procedures. Key aspects include patient immobilization to minimize motion artifacts, optimization of anesthetic agents and techniques, and maintenance of physiological stability throughout the imaging session. The review also addresses specific physiological and anesthetic necessities that may influence or interfere with the effective functioning of the injected radiotracer. Apart from strategies and protocols that can be adapted for the safe delivery of anesthesia, this review highlights vital aspects of radiation safety for anesthesiologists working in PET/MRI.
Keywords: PET/MRI; anesthesia; radiation safety